Isolation and evolutionary analysis of Australasian topotype of bluetongue virus serotype 4 from India - Reddy, Y. Vishnuvardhan; Susmitha, B.; Patil, S.; Krishnajyothi, Yadlapati; Putty, Kalyani; Ramakrishna, K.V.; Sunitha, G.; Devi, B.V.; Kavitha, K.; Deepthi, B.; Krovvidi, S.; Reddy, Y.N.; et al. (Wiley, 2017)
Bluetongue (BT) is a Culicoides-borne disease caused by several serotypes of bluetongue virus (BTV). Similar to other insect-borne viral diseases, distribution of BT is limited to distribution of Culicoides species competent to transmit BTV. In the tropics, vector activity is almost year long, and hence, the disease is endemic, with the circulation of several serotypes of BTV, whereas in temperate areas, seasonal incursions of a limited number of serotypes of BTV from neighbouring tropical areas are observed. Although BTV is endemic in all the three major tropical regions (parts of Africa, America and Asia) of the world, the distribution of serotypes is not alike. Apart from serological diversity, geography-based diversity of BTV genome has been observed, and this is the basis for proposal of topotypes. However, evolution of these topotypes is not well understood. In this study, we report the isolation and characterization of several BTV-4 isolates from India. These isolates are distinct from BTV-4 isolates from other geographical regions. Analysis of available BTV seg-2 sequences indicated that the Australasian BTV-4 diverged from African viruses around 3,500 years ago, whereas the American viruses diverged relatively recently (1,684 CE). Unlike Australasia and America, BTV-4 strains of the Mediterranean area evolved through several independent incursions. We speculate that independent evolution of BTV in different geographical areas over long periods of time might have led to the diversity observed in the current virus population.